2017
DOI: 10.1016/j.jshs.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hamstring flexibility on peak hamstring muscle strain in sprinting

Abstract: BackgroundThe effect of hamstring flexibility on the peak hamstring muscle strains in sprinting, until now, remained unknown, which limited our understanding of risk factors of hamstring muscle strain injury (hamstring injury). As a continuation of our previous study, this study was aimed to examine the relationship between hamstring flexibility and peak hamstring muscle strains in sprinting.MethodsTen male and 10 female college students participated in this study. Hamstring flexibility, isokinetic strength da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
0
27
0
4
Order By: Relevance
“…Several studies have reported peak lengthening velocity at the transition from knee flexion to extension, and a second, smaller peak in lengthening velocity has been described closer to terminal swing . During terminal swing, the BFlh reaches peak length and strain at approximately 112% of upright standing muscle length . Just prior to foot strike, the BFlh starts to shorten as the hip extends and the knee flexes in preparation for foot strike .…”
Section: Musculotendon Length Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported peak lengthening velocity at the transition from knee flexion to extension, and a second, smaller peak in lengthening velocity has been described closer to terminal swing . During terminal swing, the BFlh reaches peak length and strain at approximately 112% of upright standing muscle length . Just prior to foot strike, the BFlh starts to shorten as the hip extends and the knee flexes in preparation for foot strike .…”
Section: Musculotendon Length Changesmentioning
confidence: 99%
“…17 During terminal swing, the BFlh reaches peak length and strain at approximately 112% of upright standing muscle length. [17][18][19]22,52 Just prior to foot strike, the BFlh starts to shorten as the hip extends and the knee flexes in preparation for foot strike. [17][18][19]49 The hip continues to extend throughout stance, and the knee flexes for the first half, before starting to extend.…”
Section: Musculotendon Length Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The follow-up study further demonstrated that peak strains of hamstring muscle-tendon units in sprinting were significantly correlated to hamstring optimal lengths and flexibility score. 13 These studies support hamstring flexibility as a predicator of peak strains in sprinting. However, due to the cross-sectional nature of previous investigations, these studies did not provide any evidence that hamstring optimal lengths could be altered by altering hamstring flexibility.…”
Section: Introductionmentioning
confidence: 58%